2017
DOI: 10.1111/brv.12341
|View full text |Cite
|
Sign up to set email alerts
|

Cephalopod embryonic shells as a tool to reconstruct reproductive strategies in extinct taxa

Abstract: An exhaustive study of existing data on the relationship between egg size and maximum size of embryonic shells in 42 species of extant cephalopods demonstrated that these values are approximately equal regardless of taxonomy and shell morphology. Egg size is also approximately equal to mantle length of hatchlings in 45 cephalopod species with rudimentary shells. Paired data on the size of the initial chamber versus embryonic shell in 235 species of Ammonoidea, 46 Bactritida, 13 Nautilida, 22 Orthocerida, 8 Tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 95 publications
(103 reference statements)
1
20
0
Order By: Relevance
“…3 ). Laptikhovsky, Nikolaeva & Rogov (2017) also concluded that the evolution of reproductive strategies in cephalopods in the geological past was marked by an increasing abundance of small-egged taxa, which agrees with the findings in this study.…”
Section: Discussionsupporting
confidence: 92%
“…3 ). Laptikhovsky, Nikolaeva & Rogov (2017) also concluded that the evolution of reproductive strategies in cephalopods in the geological past was marked by an increasing abundance of small-egged taxa, which agrees with the findings in this study.…”
Section: Discussionsupporting
confidence: 92%
“…S4). While a relationship between initial egg size and hatchling DML has been described (Laptikhovsky et al 2018), as well as negative correlations with egg density (removed eggs in petri dishes; Villanueva et al 2011), a positive correlation between number of eggs and DML or YV has not been reported for multi-egg per egg capsule squids to our knowledge.…”
Section: A Note On Egg Numbermentioning
confidence: 87%
“…Cephalopods generally occupy the same set of ecological niches as teleost fishes, interacting with them as predators, prey, and competitors throughout evolutionary history (Packard 1972; Tanner et al 2017). This led to a kind of “parallel evolution” from heavily armored ancestors with an external shell/skeleton and large eggs to modern fast-swimming teleosts and coleoids with internal skeleton/shell only and a range of reproductive strategies based on small to medium-sized eggs (Laptikhovsky et al 2017). However, the cephalopod Bauplan , that of a mollusk rather than a vertebrate, provided them with a very different set of morphological possibilities to solve particular evolutionary and ecological problems.…”
Section: Introductionmentioning
confidence: 99%